Paul the Theologian: Major Motifs in Pauline Theology - Beker, Johan Christiaan (Interpretation, 1989)
Apparent tensions, even contradictions, within the letters of Paul have led some to abandon the attempt to find coherence in his theology, and others to locate it in his psychological make-up lather than his thought, neither solution represents an adequate response to the apostle's theological reflections